Mechanisms of lipid extraction from skin lipid bilayers by sebum triglycerides - Tascini,AS; Noro,MG; Seddon,JM; Chen,R; Bresme,F (Physical Chemistry Chemical Physics, 2019)
The skin surface, our first barrier against the external environment, is covered by the sebum oil, a lipid film composed of sebaceous and epidermal lipids, which is important in the regulation of the hydration level of our skin. Here, we investigate the pathways leading to the transfer of epidermal lipids from the skin lipid bilayer to the sebum. We show that the sebum triglycerides, a major component of sebum, interact strongly with the epidermal lipids and extract them from the bilayer. Using microsecond time scale molecular dynamics simulations, we identify and quantify the free energy associated with the skin lipid extraction process.